Phytoremediation of Lead, Arsenic and Chromium Polluted Soil Using Opuntia spp. (Dilang-Baka) - Paolo Angelo Pitagan; Klavejn Melendres; Annie Abonita; Kimberly Joy Escaño-Alcaraz (SEAMEO BIOTROP, 2023)
Phytoremediation capabilities of Opuntia spp. were tested on heavy metal polluted soil collected in a metallurgical factory in Carmona Cavite. Initial soil testing shows traces of Arsenic: 8.48 mg/Kg, Chromium: 116 mg/Kg, and Lead: 79 mg/Kg. pH and moisture are neutral and dry. Opuntia was compared to A. vera, within two months. Final results show both can decrease concentrations of Arsenic and Lead but Chromium from Opuntia have increased concentration might be due to the reduction of Cr(VI) to Cr(III).